Enterotype-stratified gut microbial signatures in MASLD and cirrhosis based on integrated microbiome data - Yuan, Heng; Zhou, Junyu; Wu, Xuangao; Wang, Shiwei; Park, Sunmin (Frontiers in Microbiology, 2025)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) is a growing global health challenge, characterized by significant variability in progression and clinical outcomes. While the gut microbiome is increasingly recognized as a key factor in liver disease development, its role in disease progression and associated mechanisms remains unclear. This study systematically investigated the gut microbiota’s role in MASLD and liver cirrhosis progression, focusing on individual bacterial strains, microbial community dynamics, and functional characteristics across different enterotypes.MethodsPublicly available next-generation sequencing(NGS) datasets from healthy individuals and patients with MASLD and cirrhosis were analyzed. Enterotype classification was performed using principal component analysis, with advanced bioinformatics tools, including Linear Discriminant Analysis Effect Size (LEfSe), eXtreme Gradient Boosting (XGBoost), and Deep Cross-Fusion Networks for Genome-Scale Identification of Pathogens (DCiPatho), to identify differentially abundant microbes and potential pathogens. Microbial co-occurrence networks and functional predictions via PICRUSt2 revealed distinct patterns across enterotypes.Results and discussionThe Prevotella-dominated(ET-P) group exhibited a 33% higher cirrhosis rate than the Bacteroides-dominated(ET-B) group. Unique microbial signatures were identified: Escherichia albertii and Veillonella nakazawae were associated with cirrhosis in ET-B, while Prevotella copri was linked to MASLD. In ET-P, Prevotella hominis and Clostridium saudiense were significantly associated with cirrhosis. Functional analysis revealed reduced biosynthesis of fatty acids, proteins, and short-chain fatty acids (SCFAs), coupled with increased lipopolysaccharide(LPS) production and altered secondary bile acid metabolism in MASLD and cirrhosis patients. There were significant microbial and functional differences across enterotypes in MASLD and cirrhosis progression, providing critical insights for developing personalized microbiome-targeted interventions to mitigate liver disease progression.